2008
DOI: 10.1111/j.1524-4733.2007.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Measures of the Impact of Hypothyroidism on Quality of Life and Symptoms: The ThyDQoL and ThySRQ

Abstract: Both the ThyDQoL and ThySRQ are highly acceptable to patients with hypothyroidism and have good internal consistency reliability. Their sensitivity to change now needs to be evaluated in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 25 publications
5
61
2
1
Order By: Relevance
“…Dry skin was reported by 63% of the patients. This ranged from 39 to 95% in other studies reporting on symptoms in hypothyroidism (2,5,6,10,14,17). Hair loss was observed in 30% of all cases, but this symptom had a high diagnostic odds value because only 9% of euthyroid controls reported that complaint.…”
Section: Clinical Studymentioning
confidence: 93%
See 2 more Smart Citations
“…Dry skin was reported by 63% of the patients. This ranged from 39 to 95% in other studies reporting on symptoms in hypothyroidism (2,5,6,10,14,17). Hair loss was observed in 30% of all cases, but this symptom had a high diagnostic odds value because only 9% of euthyroid controls reported that complaint.…”
Section: Clinical Studymentioning
confidence: 93%
“…Other studies also report that tiredness/fatigue/lethargy was the most common of all symptoms in hypothyroidism (4,14,27,28,29,30). Interestingly, tiredness only ranked with the 11th highest LRC but the lowest LRK.…”
Section: Symptoms In Hypothyroidismmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies have examined patient quality of life (QoL) related to the thyroid disorders and evaluated this aspect before and after treatment. The majority of studies investigated the correlation between QoL and hormone changes [8][9][10]. One study highlighted the psychological changes rather than appearance or worsening of the tiredness or asthenia [11].…”
Section: Introductionmentioning
confidence: 99%
“…Basic clinical data, consisting of serum thyrotropin (TSH) and free thyroxine (fT4) levels, clinical hypothyroidism scores (7,8), and underactive thyroid-dependent quality of life and perceived impact scales (ThyDQoL and ThySRQ) (9), were collected at each visit. TSH was measured using immunochemiluminescence on a Beckman Coulter Unicell Dxi platform.…”
Section: Study Measuresmentioning
confidence: 99%